2023
DOI: 10.1002/adhm.202301396
|View full text |Cite
|
Sign up to set email alerts
|

Toward Corneal Limbus In Vitro Model: Regulation of hPSC‐LSC Phenotype by Matrix Stiffness and Topography During Cell Differentiation Process

Abstract: A functional limbal epithelial stem cells (LSC) niche is a vital element in the regular renewal of the corneal epithelium by LSCs and maintenance of good vision. However, little is known about its unique structure and mechanical properties on LSC regulation, creating a significant gap in development of LSC‐based therapies. Herein, the effect of mechanical and architectural elements of the niche on human pluripotent derived LSCs (hPSC‐LSC) phenotype and growth is investigated in vitro. Specifically, three formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…It has been well-established that cell behavior is directly influenced by both the stiffness of the substrates upon which they reside; however, relatively few studies have focused on the corneal epithelium ( Alauzun et al, 2010 ; Kauppila et al, 2023 ; Klenkler et al, 2010 ). A recent study demonstrated that corneal epithelial cells cultured on stiff substrates (~1.0 MPa) composed of polydimethylsiloxane (PDMS) demonstrated higher proliferative indices (phosphorylated ERK, Ki67) and higher expression of cytokeratin 3, a marker of epithelial cell maturity ( Masterton and Ahearne, 2019 ).…”
Section: Corneal Epitheliummentioning
confidence: 99%
“…It has been well-established that cell behavior is directly influenced by both the stiffness of the substrates upon which they reside; however, relatively few studies have focused on the corneal epithelium ( Alauzun et al, 2010 ; Kauppila et al, 2023 ; Klenkler et al, 2010 ). A recent study demonstrated that corneal epithelial cells cultured on stiff substrates (~1.0 MPa) composed of polydimethylsiloxane (PDMS) demonstrated higher proliferative indices (phosphorylated ERK, Ki67) and higher expression of cytokeratin 3, a marker of epithelial cell maturity ( Masterton and Ahearne, 2019 ).…”
Section: Corneal Epitheliummentioning
confidence: 99%
“…In this study, we used one human embryonic stem cell (hESC) line Regea08/017 (hereafter, "hESC") and two human induced pluripotent stem cell (hiPSC) lines WT001.TAU.bB2 and WT003.TAU.bC (hereafter, "hiPSC1" and "hiPSC2", respectively) for differentiation toward LSCs with previously established protocol (Hongisto et al, 2017) (Figure 1A). The hESC line has been used for the initial establishment of the method (Hongisto et al, 2017;Mikhailova et al, 2014) and since then, has served as our golden standard line with consistently good performance in various experimental settings (Kauppila et al, 2023;Koivusalo et al, 2019;Sorkio et al, 2018;Vattulainen et al, 2019Vattulainen et al, , 2021. The hiPSC1 line has been used for hPSC-LSC differentiation in one previous study (Vattulainen et al, 2021), while hiPSC2 is a newly established line (characterization described in Supplementary File 1).…”
Section: Single-cell Rna-seq Recapitulates the Temporal Marker Gene E...mentioning
confidence: 99%